Exploring Motivational Factors For Muslims' Cash Waqf Participation: : A Case Study In Selangor, Malaysia - Mohamad Isa Abd Jalil; Ahmad Aizuddin Hamzah; Imran Mehboob Shaikh; Md Hafizi Ahsan; Joehan Joehari William (ResearchGate, 2023)
The Muslim population in Malaysia has long followed the practice of paying monetary waqf to mosques. However, no prior research has revealed the characteristics that drive donors to provide cash waqf. As a result, this research aims to investigate the factorsthat motivate Muslims in Selangor to pay monetary waqf to mosques. This study is deductive quantitative survey research in which the conceptual model was developed based on theory and empirical findings. To evaluate data for research utilising Structural Equation Modelling (SEM), 200 sample questionnaires were collected and analysed using Analysis of Moment Structure (AMOS). This study discovered that the characteristics, attitudes, subjective norms, and religiosity greatly influenced the intention of Muslims in Selangor, Malaysia, to pay cash waqf to a mosque as a result of data analysis. This study should have a theoretical impact by empirically contributing reference information to the body of knowledge in the field of waqf